2014
DOI: 10.1371/journal.pgen.1004752
|View full text |Cite
|
Sign up to set email alerts
|

Gene Pathways That Delay Caenorhabditis elegans Reproductive Senescence

Abstract: Reproductive senescence is a hallmark of aging. The molecular mechanisms regulating reproductive senescence and its association with the aging of somatic cells remain poorly understood. From a full genome RNA interference (RNAi) screen, we identified 32 Caenorhabditis elegans gene inactivations that delay reproductive senescence and extend reproductive lifespan. We found that many of these gene inactivations interact with insulin/IGF-1 and/or TGF-β endocrine signaling pathways to regulate reproductive senescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 32 publications
1
53
0
Order By: Relevance
“…Because of the crucial role of the reproductive system in regulating C. elegans longevity, we applied a high-throughput screening strategy different from the conventional method that interrupts reproduction. We selected the sqt-3(e2117) collagen mutant of C. elegans that reproduces normally but is embryonically lethal at 25 °C (Wang et al, 2014). Using this mutant, we performed the primary screen at the restrictive temperature to avoid labor-intensive animal transfer without interrupting normal reproduction (Figure S1D and E).…”
Section: Resultsmentioning
confidence: 99%
“…Because of the crucial role of the reproductive system in regulating C. elegans longevity, we applied a high-throughput screening strategy different from the conventional method that interrupts reproduction. We selected the sqt-3(e2117) collagen mutant of C. elegans that reproduces normally but is embryonically lethal at 25 °C (Wang et al, 2014). Using this mutant, we performed the primary screen at the restrictive temperature to avoid labor-intensive animal transfer without interrupting normal reproduction (Figure S1D and E).…”
Section: Resultsmentioning
confidence: 99%
“…Mutation of the daf-2 insulin/IGF-1 receptor increases C. elegans lifespan [34] and delays reproductive senescence [35, 36] and gonad degeneration [20, 37]. One possibility is that daf-2(−) suppresses gonad degeneration by reducing PA. daf-2 mutants fall broadly into two classes: class 1, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…In an evolutionary context, we assume that senescence is partially genetically determined (Kirkwood and Austad ; Patridge and Gems ; Nussey et al ; Kowald and Kirkwood ; Reichard ), and several studies have confirmed the heritability of individual senescence patterns (Arking ; Charmantier et al ; Wilson et al ; Wang et al ). The effect of developmental environment on reproductive senescence may therefore represent a “genotype by past‐environment” interaction.…”
Section: Discussionmentioning
confidence: 99%